PRODUCTION PLANNING AND CONTROL FOR MECHANICAL ENGINEERING TECHNOLOGY - TENGKU NUR AZILA BINTI RAJA MAMAT,; RAHIM BIN JAMIAN,; SALWA BINTI MAHMOOD, (2023)
"Production Planning and Control for Mechanical Engineering Technology" is a textbook thoroughly created to cater to the academic needs of Mechanical Engineering Technology students at Universiti Tun Hussein Onn Malaysia (UTHM). It represents a culmination of extensive dedication and experience in the teaching of Production Planning and Control (PPC) course, a pivotal domain within the field of industrial engineering.With a rich teaching background more than five years, the author recognized the imperative need for a comprehensive resource that captures the evolving complexities and advancements within the realm of production planning and control. This realization served as the driving force behind the creation of this textbook, strategically structured to provide a profound and well-organized understanding of the course.The book is structured into seven comprehensive sections, each serving as a gateway into a vital aspect of production planning and control, namely fundamental of forecasting, inventory management, aggregate planning, resource planning, short-term scheduling, and lean production.Embark on an enriching academic journey through the pages of this textbook, digging into the depths of production planning and control. Acquire not only theoretical expertise but also practical understanding, equipping yourself for a future where industry expectations meet academic excellence.